Impact of Mindfulness-Based Stress Management Treatment on the Psychological Disorders of Individuals with Chronic Medical Problems - Abdus Salam, Mehwish Butt, Allina Khan, Sumaiya Zulfiqar, Kashifa Ehsan, Naveed Fazal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The goal of this research would have been to look at the impact of mindfulness-based stress decrease on despair, stress, in addition emotional stress in individuals having various chronic medical conditions. Methods: To investigate the benefits of MBSR on depression, anxiety, and emotional stress, a review and meta-analysis were conducted. The impact of study quality on possessions of MBSR remained investigated. Results: Ten researches randomized control trials have been included. The total impact size on sadness was 0.28, showing that MBSR had little effect on mental health. Anxiety had an effective dose of 0.48. The validity of the research, however, was shown to reduce this impact magnitude. When low-quality research was eliminated, an effect size of 0.26 on stress was discovered. Emotional trauma also had a minor impact size (0.35). Conclusion: It is possible to infer that MBSR has only a minor impact on despair, concern, also psychological discomfort in individuals through chronic somatic conditions. The use of MBSR in behavioral treatment can increase effectiveness of mindfulness-grounded therapies. Keywords: Mindfulness-Based Stress Management Treatment, Anxiety, emotional trauma, medical disease.